AN EXAMPLE OF DIVAN WRITTEN BY SABRİ OF MALATYA IN THE TERMS OF LOVE FOR AHL-UL-BAYT IN OUR LITERATURE - Saadettin KEKLİK (Fırat University, 2019)
An Islamic term Ahl-ul-Bayt which means a household is used for the family members of Hz. Muhammed. Love and respect for Prophet himself and his family has been an important issue in Divan literature too. On the other hand, also known as a case of Karbala Hz. Huseyin’s martyrdom in poems and prose works were written. As with many poets who express their love of Ahl-ul-Bayt, one of them is Sabri of Malatya. The aim of the study is to reveal the love of Ahl-ul-Bayt which reflects to the poet’s poetry with the motion of Sabri Divan. It is predicted that Sabri of Malatya had lived between second half of 19th century and first quarter of 20th century. Sabri was related to Kadiriyye tarikat and he wrote sufi poetries. The only existing manuscripts of Sabri Divan is at Süleymaniye Library and registered with the number “Kemal Edip Kürkçüoğlu 48”. The only study about Sabri and his work is belonged to Savran. There are totally 264 poems in Sabri Divan. 242 of them are lyric poems (gazel), 1 is murabba, 1 is muhammes, 3 of them are museddes and 3 of them are in mufred verse format. 14 poems are written in syllabic meter. The love of Ahl-ul-Bayt in Sabri Divan is examined under the headings of Hz. Ali, Hz. Hasan, Hz. Huseyin and Karbala, Yezid and Twelve Imams. Sabri has included poems focusing on virtues and properties of Ahl-ul-Bayt at about 20 places in his